Compatibility study between aluminium alloys and alternative recycled ceramics for thermal energy storage applications. (15th June 2018) - Xu, Haoxin; Dal Magro, Fabio; Sadiki, Najim; Mancaux, Jean-Marie; Py, Xavier; Romagnoli, Alessandro
Highlights: Conducted high temperature corrosion tests at 1000 °C for 100 h. Performed ESEM and XRD characterization for reliable post-corrosion analysis. First time to report the compatibility between molten al-based alloys and three recycled ceramics. Concluded possible encapsulation materials from wastes for molten aluminium alloys. Abstract: Recycled ceramics from industrial wastes, compared with traditional high-purity ceramics, present high market potential as refractory materials due to their low cost production process with very low environmental impacts. However, there still exists a research gap of how recycled ceramics behave while in contact with liquid metal. In order to study the feasibility of using recycled ceramics as the encapsulation material in the application of high temperature Latent Heat Thermal Energy Storage system, this paper investigates the compatibility of recycled ceramics with three kinds of aluminium-based alloys at high temperature, with a comparison to the corrosion resistant behaviour of alumina. The recycled ceramics explored include Cofalit from asbestos containing waste, blast furnace slags from steel production, and coal fly ashes sintered ceramics from incineration plants. The study consists of a steady state thermal treatment of ceramic samples in contact with the three different alloys at 1000 °C for 100 h, and a post instrumental characterization of ceramic samples by Environmental Scanning Electron Microscopy, Energy Dispersive Spectrometry and X-ray diffractometer, to understand the chemical and structural transformation of the ceramics. Results demonstrate that Cofalit shows chemical stability with Al99% but instability with AlSi5% and AlSi12%. Blast furnace slag presents quite good thermochemical stability towards molten AlSi5% and AlSi12%. Coal fly ashes sintered ceramics are highly interactive towards all three aluminium alloys. In conclusion, besides alumina, Cofalit is recommended as alternative encapsulation material for molten Al99%, while blast furnace slag being recommended for molten AlSi5% and AlSi12%.